2012
DOI: 10.1161/circep.111.969592
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Data Predictors of a Left Ventricular Outflow Tract Origin of Idiopathic Ventricular Tachycardia With V 3 Transition and Septal Earliest Activation

Abstract: Background-The proximity of the outflow tracts (OTs) frequently results in an overlap in surface electrocardiographic features of ventricular arrhythmias originating from this anatomic region, particularly when the transition occurs in lead V 3 . In addition, no reliable criteria to discriminate between a right ventricular OT (RVOT) and a left ventricular OT (LVOT) site of origin (SOO) are derived from intracardiac mapping. Methods and Results-A series of 15 patients underwent ablation because of OT ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
39
2
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 18 publications
0
39
2
1
Order By: Relevance
“…[2][3][4][5][6][7][8][9] However, their accuracy has been questioned recently, especially when the transition in the precordial leads occurs in V 3 10 and/or the maximum electrogram (EG) precocity is located in the septal RVOT. 11 Herczku et al 11 recently described different activation patterns in the septal RVOT in VAs arising from OT regions depending on right vs left origin. However, despite the high sensitivity and specificity found for these activation patterns, they resulted from a detailed electroanatomic map (EAM) of the septal RVOT in a small series of patients, in which not all of the possible locations were well represented.…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5][6][7][8][9] However, their accuracy has been questioned recently, especially when the transition in the precordial leads occurs in V 3 10 and/or the maximum electrogram (EG) precocity is located in the septal RVOT. 11 Herczku et al 11 recently described different activation patterns in the septal RVOT in VAs arising from OT regions depending on right vs left origin. However, despite the high sensitivity and specificity found for these activation patterns, they resulted from a detailed electroanatomic map (EAM) of the septal RVOT in a small series of patients, in which not all of the possible locations were well represented.…”
Section: Introductionmentioning
confidence: 99%
“…The right ventricular outflow tract (RVOT) myocardium is frequently the source of VPBs or idiopathic ventricular tachycardia. [1][2][3] Patients with frequent RVOT VPBs often have no structural heart disease and have a benign outcome. If symptomatic or associated with left ventricular (LV) dysfunction, the VPBs can be treated conservatively with antiarrhythmic drugs (AADs) 4,5 ; however, drug therapy may predispose to recurrence and is associated with risks including proarrhythmia.…”
mentioning
confidence: 99%
“…; (2) previous AADs therapy; (3) evidence of any structural heart disease; (4) hyperthyroidism or electrolyte disturbance; (5) drug toxicity; (6) diabetes mellitus; (7) blood pressure>165/100 mm Hg; (8) significant impairment of renal function; (9) QT interval>450 ms in the absence of bundle-branch block; and (10) significant atrioventricular conduction disease and left or right bundle-branch block. Of all patients screened, 330 patients were eligible for the study and provided written informed consent for participation.…”
mentioning
confidence: 99%
“…We estimated the 5-ms and 10-ms isochronal areas of earliest activation in this study. Several studies have looked at the 10-ms isochronal area, 6,7,16,17) but we found the 10-ms isochronal area was overly large, because it included sites with lower precocity relative to the earliest onset of PVC. Instead, we found that the 5-ms isochronal area was more accurate for detecting suitable ablation sites for VAs, and in fact, a smaller 5-ms isochronal map area was able to predict successful ablation sites of VAs in this study with statistical significance.…”
Section: Discussionmentioning
confidence: 92%
“…Therefore, it is important to construct maps of activation times preceding the QRS onset of the VAs and to identify the earliest site of activation. Isochronal mapping: Herczku, et al 16) reported that the 10-ms isochronal map area of RVOT could predict whether the site of origin was in the RVOT or LVOT in patients with outflow tract VAs with V3 transition and septal earliest activation. Acosta, et al 17) reported that both the distance between the earliest activation site of RVOT and the pulmonary vein and the 10-ms isochronal longitudinal/perpendicular diameter ratio could predict whether the site of origin was in the LVOT or RVOT in outflow tract VAs with earliest activation site in the septal RVOT.…”
Section: Discussionmentioning
confidence: 99%